Bile acid: a potential inducer of colon cancer stem cells. Issue 1 (December 2016) - Farhana, Lulu; Nangia-Makker, Pratima; Arbit, Evan; Shango, Kathren; Sarkar, Sarah; Mahmud, Hamidah; Hadden, Timothy; Yu, Yingjie; Majumdar, Adhip
Abstract Background Although the unconjugated secondary bile acids, specifically deoxycholic acid (DCA) and lithocholic acid (LCA), are considered to be risk factors for colorectal cancer, the precise mechanism(s) by which they regulate carcinogenesis is poorly understood. We hypothesize that the cytotoxic bile acids may promote stemness in colonic epithelial cells leading to generation of cancer stem cells (CSCs) that play a role in the development and progression of colon cancer. Methods Normal human colonic epithelial cells (HCoEpiC) were used to study bile acid DCA/LCA-mediated induction of CSCs. The expression of CSC markers was measured by real-time qPCR. Flow cytometry was used to isolate CSCs. T-cell factor/lymphoid-enhancing factor (TCF/LEF) luciferase assay was employed to examine the transcriptional activity of β-catenin. Downregulation of muscarinic 3 receptor (M3R) was achieved through transfection of corresponding siRNA. Results We found DCA/LCA to induce CSCs in normal human colonic epithelial cells, as evidenced by the increased proportion of CSCs, elevated levels of several CSC markers, as well as a number of epithelial–mesenchymal transition markers together with increased colonosphere formation, drug exclusion, ABCB1 and ABCG2 expression, and induction of M3R, p-EGFR, matrix metallopeptidases, and c-Myc. Inhibition of M3R signaling greatly suppressed DCA/LCA induction of the CSC marker ALDHA1 and also c-Myc mRNA expression as well as transcriptional activation of TCF/LEF. Conclusions Our results suggest that bile acids, specifically DCA and LCA, induce cancer stemness in colonic epithelial cells by modulating M3R and Wnt/β-catenin signaling and thus could be considered promoters of colon cancer.